About individual differences of word association speed in learning the languages - Nečiūnas, V. (Psichologija, 1966)
While using the modified method of association experiment the author tested the word association speed in Lithuanian (mother tongue), Russian, and foreign language. Students at medical institute were tested, total of 256 subjects. The study showed that in the end of the second study year of Russian and foreign language, the speed of association process (within the household terms) reaches in Russian 85%, in foreign language and 69% the speed of mother tongue. The comparison and analysis of association processes in mother tongue, Russian and foreign language showed that every subject has an individual speed of association process, which is determined by one’s higher nervous activity. All subjects were divided into three groups: 40 subjects with a slow verbal reaction, 151 subjects with moderate and 65 subjects with a fast verbal reaction. The analysis of study results in three groups in the last 3.5 years showed that subject group with a slow verbal reaction had a lower mean of examination grades than those with a fast verbal reaction (respectively 3.78 and 4.1). This lows a statement that in learning process and during the examinations there was no appropriate focus on individual differences in students and no corresponding work speed or methods were applied.